2021
DOI: 10.18805/ijare.a-5661
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic Fungal Screening against Two Spotted Spider Mites, Tetranychus urticae Koch in Tomato and Broad Mite, Polyphagotarsonemus latus (Banks) in Chilli

Abstract: Background: Entomopathogenic fungi are microorganisms that specifically infect and often kill insects and other arthropods. Most are non-pathogenic to plants and relatively non-toxic to humans and animals. Use of fungal entomopathogens can be an alternative to insecticides and could help in bio-intensive pest management. The current study aimed to study the pathogenicity of entomopathogenic fungal isolates against two Spotted Spider Mites, Tetranychus urticae Koch in tomato and broad Mite, Polyphagotarsonemus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The mortality of aphids was counted every 24 h up to seven days (Fig 1 D-F . Dead aphids were collected daily and transferred to a moist filter paper in a self-sealed Petri dish; once the dead aphid produced mycelial growth, they were considered for the mortality count (Parveen et al, 2021). The mortality data were then corrected using Abbott's formula (Abbott 1925).…”
Section: Median Lethal Concentration (Lc 50 ) Assessmentmentioning
confidence: 99%
“…The mortality of aphids was counted every 24 h up to seven days (Fig 1 D-F . Dead aphids were collected daily and transferred to a moist filter paper in a self-sealed Petri dish; once the dead aphid produced mycelial growth, they were considered for the mortality count (Parveen et al, 2021). The mortality data were then corrected using Abbott's formula (Abbott 1925).…”
Section: Median Lethal Concentration (Lc 50 ) Assessmentmentioning
confidence: 99%
“…In other words, I. fumosorosea was not as effective as B. bassiana and M.anisopliae (Acosta-Robles et al, 2019). Parveen et al (2021) in an investigation to screen fungal isolates of B. bassiana, M. anisopliae and Lecanicillium lecanii against TSSM and broad mites found that both agricultural mites were susceptible to all fungal isolates tested. However, isolates of B. bassiana showed the highest mortality in TSSM and M. anisopliae showed the same in broad mites.…”
Section: Pathogensmentioning
confidence: 99%
“…Webbing's primary function is to protect eggs, the colony and these webs can be seen with the naked eye. One of the most critical aspects in agricultural pest growth and reproduction is the nutritional quality of the host plant (Motahari, et al, 2014;Parveen et al, 2021). It causes changes in the biochemical composition of the host plant in addition to mechanical and physiological harm.…”
Section: Introductionmentioning
confidence: 99%